2003
DOI: 10.5194/nhess-3-637-2003
|View full text |Cite
|
Sign up to set email alerts
|

Neutron flux variations near the Earth’s crust. A possible tectonic activity detection

Abstract: Abstract. The present work contains some results of observations of neutron flux variations near the Earth’s surface. The Earth’s crust is determined to be a significant source of thermal and slow neutrons, originated from the interaction between the nuclei of the elements of the Earth’s crust and the atmosphere and α-particles, produced by decay of radioactive gases (Radon, Thoron and Actinon). In turn, variations of radioactive gases exhalation is connected with geodynamical processes in the Earth’s crust, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 1 publication
2
20
0
Order By: Relevance
“…3) confirms the conclusion (Kuzhevskij et al, 2002a;Volodichev et al, 2002) about the important contribution made by the Earth's crust to the total flux of thermal and slow neutrons in its vicinity. This conclusion was also obtained by another method (Kuzhevskij et al, 2001b;Volodichev et al, 2002) and it demonstrated the connection between neutron flux varitaions near the Earth's crust and its dynamics. This function confirms that this input of the Earth's crust comes through mainly during different types of splashes, which occur in the Earth's crust (splash periods).…”
Section: Analysis Of the Experimental Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…3) confirms the conclusion (Kuzhevskij et al, 2002a;Volodichev et al, 2002) about the important contribution made by the Earth's crust to the total flux of thermal and slow neutrons in its vicinity. This conclusion was also obtained by another method (Kuzhevskij et al, 2001b;Volodichev et al, 2002) and it demonstrated the connection between neutron flux varitaions near the Earth's crust and its dynamics. This function confirms that this input of the Earth's crust comes through mainly during different types of splashes, which occur in the Earth's crust (splash periods).…”
Section: Analysis Of the Experimental Resultssupporting
confidence: 60%
“…Analysis of this approximation permits us to study properties of the neutron source and the nature of flux variations. Earlier experiments (Kuzhevskij, 2000(Kuzhevskij, , 2001b, which included studies of the neutron flux in different geographic locations (on balloons: Apatity, Kolskij peninsula; Dolgoprudny, Moscow region; Ryl'sk, Kaluga region; groundbased experiments at different altitudes above sea level: Moscow; Golitsino, Moscow region; Seliger Lake, Tver' region; Pamir, Tadgikistan; Tyan-Shan, Kazakhstan) have shown that there seems to be at least two neutron sources near the Earth's crust. The first source is the generation of neutrons in the Earth's atmosphere as a result of interactions between high-energy space particles with nuclei of the different elements of the Earth's atmosphere.…”
Section: Obtained Thatmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, Kuzhevskij et al . [] moved the detector over a lake and interprets that the signal strength is hardly sensitive to neutrons from the land side at distances greater than 200 m. In the last years, many experiments with the COSMOS detector have been performed across a water‐land boundary by the group of M. Zreda. First data from Oceanside Pier (California, USA) indicate that the sensitive distance is on the order of 100–200 m at sea level.…”
Section: Resultsmentioning
confidence: 99%
“…Presently, there are solid evidences that dynamic processes linked to terrestrial deformations show up in variations in the fluxes of slow neutrons and charged particles (Volodichev et al 2003;Kuzhevskij et al 2003). Continuous monitoring of the intensity of these particle fluxes can be helpful in solving the problem of earthquake prediction.…”
Section: Introductionmentioning
confidence: 99%